Analisis Penggunaan Game Edukasi Wordwall Pada Pelajaran IPS Terhadap Kemampuan Pemecahan Masalah Siswa Kelas IV SD - Elis Rina Nuraeni; Tin Rustini; Agus Mulyana (Jurnal Bintang Pendidikan Indonesia, 2023)
This research has been hampered by a lack of problem-solving skills in elementary school students, a shortage of learning enthusiasm and less experience with digital learning. The purpose of this research is to find out the use of wordwal educational games against student problem-solving skills. Methods used analysis with design qualitative research descriptive. Data collection techniques using tests, interviews, and observations. The subject of this research is 20 students of 4th grade SDN Sukarasa. Research results show that (1) using wordwall educational games on learning can develop problem-solving skills, and (2) using Wordwall education games can train entire indicators of student problem solving skills. Proved by the average score obtained by Oleg students among them the highest score with an average score of 2.6 - 3 total of 9 students, average score 2 - 2.5 total 9 students and average score 0 - 1.9 total of 2 students.